Pelatihan building information modeling bagi Guru Sekolah Menengah Kejuruan di DIY dan Jawa Tengah - Hastutiningsih, Arum Dwi; Pramudiyanto, Pramudiyanto; Elviana, Elviana; Raharjo, Nuryadin Eko (Penamas: Journal of Community Service, 2024)
This community service aims to enhance the digital competence of Vocational High School (SMK) teachers in the Special Region of Yogyakarta (DIY) and Central Java through Building Information Modeling (BIM) training. BIM is a crucial technology in the digital era, especially in the construction, architecture, and civil engineering sectors, as it facilitates better collaboration in project planning, design, and management. Through this training, teachers are expected to integrate BIM technology into the learning process to help students understand practical concepts relevant to the workforce. The results of this activity show an increase in teachers' competency in using BIM, as well as their readiness to apply technology-based learning methods in the classroom.